CYP11B1 gene polymorphisms and susceptibility to ischemic stroke in a Chinese Han population - Liu, Gaowen; Duan, Ying (Frontiers in Neuroscience, 2022)
Objectives: Ischemic stroke (IS) is a major cause for death and disability. Previous studies have confirmed that CYP11B1 is closely associated with IS. This research aimed to study the impact of CYP11B1 gene polymorphisms on IS susceptibility. Methods: We genotyped six single nucleotide polymorphisms (SNPs) (including rs4736312, rs5017238, rs5301, rs5283, rs6410, and rs4534) of CYP11B1 in peripheral blood samples from IS and control populations. The association between SNPs and IS risk was analyzed by logistic regression analysis. The roles of SNP-SNP interactions on IS were determined by multifactor dimensionality reduction (MDR) method. Results: Our study showed that rs5283 was associated with increased susceptibility to IS (OR 1.81, p= 0.012). On the contrary, rs6410 had a protective influence on IS risk (OR 0.56, p= 0.020). Stratified analyses indicated that rs5283 could enhance the risk of IS in subjects aged> 63 years (OR 2.41, p= 0.011), in women (OR 3.31, p= 0.001), non-smoking (OR 1.64, p= 0.005), and complicated with hypertension (OR 2.07, p= 0.003). Whereas rs6410 was related to a lower susceptibility to IS in people aged> 63 years (OR 0.43, p= 0.032), in women (OR 0.30, p= 0.006), non-smoking (OR 0.42, p= 0.017), and complicated with hypertension (OR 0.52, p= 0.022). Besides, rs4736312 reduced IS susceptibility in non-smoking (OR 0.69, p= 0.031). Rs4534 had risk-decreasing impact on IS in non-drinking (OR 0.54, p= 0.016). Moreover, MDR analysis given that the best prediction model for IS was rs5283. Conclusion: This study revealed that CYP11B1 gene polymorphisms strongly correlated with IS in the Chinese Han population.